Preferences of Engineering Alumni at the Universidad Cooperativa de Colombia, Popayán Campus, Regarding Areas of Knowledge for a Post-Graduate Program - De la Torre Solarte, Gabriel; Padilla Moreno, Rafael María (Ingeniería Solidaria, 2014)
This article is a product of the research study titled “Evaluation of existing under-graduate and post-graduate programs in the Popayan branch of the Universidad Cooperativa de Colombia and the creation of new academic programs for the Engineering Faculty”, in 2012. The authors analyzed the preferred areas of knowledge according to alumni in order to create post-graduate academic programs matching the interests and expectations of students finishing their engineering degrees. In the final section of this paper, the authors present some criteria for the creation of post-graduate course offerings that are of interest to recent alumni, and also meet their training needs.
Keywords: alumni; engineering; course offerings; post-graduate; programs